Patient-Delivered Partner Treatment for Chlamydia, Gonorrhea, and Trichomonas Infection Among Pregnant and Postpartum Women in Kenya - Unger, Jennifer A. (Sex Transm Dis, 2015)
BACKGROUND: Patient-delivered partner treatment (PDPT) for sexually transmitted infections (STIs) increases rates of partner treatment and decreases reinfection, but has not been evaluated during pregnancy. METHODS: This prospective cohort was nested within a larger study of peripartum HIV acquisition. Participants with microbiologic diagnosis of Chlamydia trachomatis, Neisseria gonorrhoeae, and/or Trichomonas vaginalis were screened for participation. Questionnaires were administered to determine PDPT acceptability and barriers. Women were reassessed at least 30 days to determine partner treatment and reinfection. Women whose partners did or did not receive PDPT were compared. RESULTS: One hundred twelve (22.2%) women in the parent cohort had a treatable STI; 78 within the PDPT study period, of whom 66 were eligible and 59 (89.3%) accepted PDPT. Fifty-one women had PDPT outcome data, 37 (73%) of whom reported partners treated with PDPT. Fourteen women (27%) refused or did not deliver partner treatment. Median age was 22 years (interquartile range, 20–26 years) and 88% were married. Compared with women who delivered PDPT, those who did not were more likely to have a partner living far away (23% vs. 0%, P = 0.004) and to report current intimate partner violence (14% vs. 0%, P = 0.02). Reported PDPT barriers included fear of partner’s anger/abuse (5%) and accusations of being STI source (5%). CONCLUSION: Patient-delivered partner treatment was acceptable and feasible for pregnant/postpartum Kenyan women and may reduce recurrent STIs in pregnancy.